A Randomized Controlled Trial of a Therapeutic Intervention for Nursing Home Residents With Dementia and Depressive Symptoms. (July 2017) - Bailey, Elaine M.; Stevens, Alan B.; LaRocca, Michael A.; Scogin, Forrest
Objective: The purpose of this study was to conduct a randomized controlled trial of a nursing home intervention to reduce depressive symptoms in residents with dementia.Method: The multicomponent intervention included group activity sessions, which used question-asking-reading (QAR), reminiscence, and cognitive-behavioral therapy techniques, as well as environmental supports and individualized behavioral activity programs. Fifty-one residents from five nursing homes participated in the study.Results: A significant difference in depressive symptoms was found, with residents in the QAR-Depression condition showing improvement compared with those in the treatment as usual condition. Residents in the treatment group also exhibited significantly higher levels of expressive verbalizations, engagement with materials, and laughter. Few differences in resident behavior occurring outside of the group activities were noted.Discussion: Findings suggest that structured group activities can positively impact a resident's psychological well-being. In addition, the QAR structure may be suitable for older adults with cognitive impairment by distributing group tasks and providing external cognitive supports.